2022
DOI: 10.1039/d2tc00322h
|View full text |Cite
|
Sign up to set email alerts
|

Interface compatibility: how to outperform classical spiro-OMeTAD in perovskite solar cells with carbazole derivatives

Abstract: Perovskite solar cells efficiency and stability are strongly impacted by the charge extraction materials. Considering high density of surface defects at the perovskite/charge transporting interfaces, passivation strategies should be optimized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…As an emerging photovoltaic technology, organic–inorganic hybrid perovskite solar cells (PVSCs) have attracted worldwide attention due to their rapid progress in power-conversion efficiency (PCE) . In the decade since the first report in 2009, the device performance has achieved an extraordinary improvement from the initial 3.8% to a certified 25.5% present efficiency, which is attributed to the outstanding optoelectronic properties of perovskite materials such as tunable band gap, high absorption coefficient, low exciton binding energy, high charge mobility, long charge carrier diffusion length, ambipolar charge-transfer capability, etc. On the way to meet the low cost, high efficiency, and reliable stability demands of commercialization, numerous works have been devoted to modulating the perovskite composition, improving the perovskite film quality, optimizing the device structure, and modifying the interface properties. Among various techniques, interface engineering plays a vital role in influencing perovskite film qualities, interface properties as well as device performance of PVSCs. , Specifically, high-performance hole-transport materials (HTMs) are urgently needed for obtaining high-performance PVSCs. …”
Section: Introductionmentioning
confidence: 99%
“…As an emerging photovoltaic technology, organic–inorganic hybrid perovskite solar cells (PVSCs) have attracted worldwide attention due to their rapid progress in power-conversion efficiency (PCE) . In the decade since the first report in 2009, the device performance has achieved an extraordinary improvement from the initial 3.8% to a certified 25.5% present efficiency, which is attributed to the outstanding optoelectronic properties of perovskite materials such as tunable band gap, high absorption coefficient, low exciton binding energy, high charge mobility, long charge carrier diffusion length, ambipolar charge-transfer capability, etc. On the way to meet the low cost, high efficiency, and reliable stability demands of commercialization, numerous works have been devoted to modulating the perovskite composition, improving the perovskite film quality, optimizing the device structure, and modifying the interface properties. Among various techniques, interface engineering plays a vital role in influencing perovskite film qualities, interface properties as well as device performance of PVSCs. , Specifically, high-performance hole-transport materials (HTMs) are urgently needed for obtaining high-performance PVSCs. …”
Section: Introductionmentioning
confidence: 99%
“…Its role consists of extracting and transporting photogenerated holes, blocking electrons and protecting the perovskite active layer from external stress such as moisture, oxygen and heat [8,10]. The chemical structure of the HTM and particularly the functional groups can also play a crucial role in the passivation of defects at the perovskite/HTM interface [11][12][13]. An ideal HTM should present suitable energy levels of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO), high hole mobility, good solubility in common organic solvents and high chemical, thermal, morphological, light and moisture stability [14].…”
Section: Introductionmentioning
confidence: 99%
“…3,6-CzDMPA-based HTMs have attracted much attention due to their interesting physicochemical properties, such as molecular glass behavior, excellent thermal stability and good solubility, and good charge transport properties [31,32]. We have extensively studied this class of HTMs in dye-sensitized solar cells (DSSCs) and PSC applications [11,[33][34][35][36][37][38]. It has been demonstrated that the terminal methoxy groups can act as a Lewis base to passivate the defect sites at the perovskite/HTM interface [11,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, pyridine and thiophene-based organic small molecules, which contain electron-rich nitrogen/sulfur atoms, are effective for interacting with uncoordinated Pb 2+ to restrict charge recombination. [27][28][29][30][31] Bipyridine as a planar molecule with an electron-withdrawing ability can construct the energy level alignment and passivate the uncoordinated Pb 2+ of perovskite to improve the charge extraction and the transport properties. 32,33 Simultaneously, some hole transport materials with good hole-extraction and hole-transport abilities based on bipyridine [34][35][36] such as F22 and F23, have been designed for PSCs to improve the device performance.…”
Section: Introductionmentioning
confidence: 99%